Pengendalian Hama Penyakit Terpadu untuk Mengurangi Kerusakan pada Tanaman Padi di Desa Mekar Sari Kecamatan Gunung Sari - Made Suma Wedastra; I Dewa Gede Suartha; Theresia Suzanna Catharina; Ida Ayu Ketut Marini; Ni Wayan Putu Meikapasa; Ida Ayu Nopiari (Universitas Mataram, 2020)
Until now farmers still use synthetic chemical pesticides in eradicating pests and diseases. On the one hand, the use of synthetic chemical pesticides is beneficial because of the poison power or the ability to kill pests and diseases that are high and fast, but the excessive use of toxic pesticides, in addition to the increasingly resistant pests and diseases to pesticide poisons, can also pollute the environment. In addition, pesticide poisons tend to increase in price, so that economically it does not increase production value. Community service is carried out in the form of agricultural counseling, carried out in Mekar Sari Village, Gunung Sari District, aiming that farmers have better knowledge and are willing to implement integrated pest and disease control (IPM) methods on rice plants. This counseling material was delivered with lecture techniques, then followed by question and answer sessions. The agricultural extension activities in Mekar Sari Village, Gunung Sari Subdistrict went smoothly and most of the extension participants were able to increase their knowledge to be better, so that they were expected to increase their understanding and be able to apply the technology